Central system of accounting information of the Czech Republic - Svoboda, Michal (Видавництво Львівської політехніки, 2011)
Since January 1st, 2010, a new accounting system in the public sector of the Czech Republic has been effective. This has changed not only the way of compilation of financial statements (now on accrual base), but also the way of their disclosure and presentation. This should be ensured by „Central System of Accounting Information of the Czech Republic“. Itsmain intent is to satisfy the information needs of all public sector financial statements users, especially general public (tax payers), European and international institutions etc.
Keywords: governmental accounting; public sector; public finance; consolidation; government